Kaempferol Inhibits Angiogenesis by Suppressing HIF-1α and VEGFR2 Activation via ERK/p38 MAPK and PI3K/Akt/mTOR Signaling Pathways in Endothelial Cells - Kim, Gi Dae (Preventive nutrition and food science, 2017)
Kaempferol has been shown to inhibit vascular formation in endothelial cells. However, the underlying mechanisms are not fully understood. In the present study, we evaluated whether kaempferol exerts antiangiogenic effects by targeting extracellular signal-regulated kinase (ERK)/p38 mitogen-activated protein kinase (MAPK) and phosphoinositide 3-kinase (PI3K)/Akt/mechanistic target of rapamycin (mTOR) signaling pathways in endothelial cells. Endothelial cells were treated with various concentrations of kaempferol for 24 h. Cell viability was determined by the 3- (4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2H-tetrazolium bromide assay; vascular formation was analyzed by tube formation, wound healing, and mouse aortic ring assays. Activation of hypoxia-inducible factor-1α (HIF-1α), vascular endothelial growth factor receptor 2 (VEGFR2), ERK/p38 MAPK, and PI3K/Akt/mTOR was analyzed by Western blotting. Kaempferol significantly inhibited cell migration and tube formation in endothelial cells, and suppressed microvessel sprouting in the mouse aortic ring assay. Moreover, kaempferol suppressed the activation of HIF-1α, VEGFR2, and other markers of ERK/p38 MAPK and PI3K/Akt/mTOR signaling pathways in endothelial cells. These results suggest that kaempferol inhibits angiogenesis by suppressing HIF-1α and VEGFR2 activation via ERK/p38 MAPK and PI3K/Akt/mTOR signaling in endothelial cells.